Late Jurassic palaeoclimatic change from clay mineralogy and gamma-ray spectrometry of the Kimmeridge Clay, Dorset, UK - Hesselbo, S; Deconinck, J; Huggett, J; Morgans-Bell, H (2009)
The Late Jurassic was a time of increasing aridity in NW Europe. Here, a new clay mineral dataset is presented from a 600 m thick composite core through the Kimmeridge Clay Formation, southern England. Clay mineral assemblages comprise mainly illite and kaolinite, with minor randomly interstratified illite- smectite mixed-layer clays. SEM observations indicate that clay minerals are mainly detrital, except in silty strata of late Tithonian age, which contain abundant pore-filling kaolinite aggregates. Th/K ratios determined from gamma-ray spectrometry mirror palaeoclimatically significant variations in kaolinite/illite ratios, with notable exception where diagenetic kaolinite occurs. Comparison with age-equivalent strata identifies regional cyclic variations in clay minerals at the 100-300 m scale. Small-scale (10-20 m) variations in clay minerals and Th/K also occur. It is proposed that the region experienced progressively intense humidity through the Kimmeridgian, followed by a return to more arid conditions during the early Tithonian. Following a mid- Tithonian peak in aridity (the 'Hudlestoni Event'), more humid climatic conditions returned prior to the development of latest Tithonian intense aridity. Late Jurassic climate was apparently subject to synchronously cyclic changes across a broad area of the Laurasian continent. Such changes could not have resulted from mountain building or continental rotations. © 2009 Geological Society of London.